XRCC1 promotes replication restart, nascent fork degradation and mutagenic DNA repair in BRCA2-deficient cells. (1st August 2020) - Eckelmann, Bradley J; Bacolla, Albino; Wang, Haibo; Ye, Zu; Guerrero, Erika N; Jiang, Wei; El-Zein, Randa; Hegde, Muralidhar L; Tomkinson, Alan E; Tainer, John A; Mitra, Sankar
Abstract: Homologous recombination/end joining (HR/HEJ)-deficient cancers with BRCA mutations utilize alternative DNA double-strand break repair pathways, particularly alternative non-homologous end joining or microhomology-mediated end joining (alt-EJ/MMEJ) during S and G2 cell cycle phases. Depletion of alt-EJ factors, including XRCC1, PARP1 and POLQ, is synthetically lethal with BRCA2 deficiency; yet, XRCC1 roles in HR-deficient cancers and replication stress are enigmatic. Here, we show that after replication stress, XRCC1 forms an active repair complex with POLQ and MRE11 that supports alt-EJ activity in vitro . BRCA2 limits XRCC1 recruitment and repair complex formation to suppress alt-EJ at stalled forks. Without BRCA2 fork protection, XRCC1 enables cells to complete DNA replication at the expense of increased genome instability by promoting MRE11-dependent fork resection and restart. High XRCC1 and MRE11 gene expression negatively impacts Kaplan–Meier survival curves and hazard ratios for HR-deficient breast cancer patients in The Cancer Genome Atlas. The additive effects of depleting both BRCA2 and XRCC1 indicate distinct pathways for replication restart. Our collective data show that XRCC1-mediated processing contributes to replication fork degradation, replication restart and chromosome aberrations in BRCA2-deficient cells, uncovering new roles of XRCC1 and microhomology-mediated repair mechanisms in HR-deficient cancers, with implications for chemotherapeutic strategies targeting POLQ and PARP activities.